1980
DOI: 10.1093/nar/8.13.2885
|View full text |Cite
|
Sign up to set email alerts
|

The complete amino acid sequence of human fibroblast interferon as deduced using synthetic oligodeoxyribonucleotide primers of reverse transcriptase

Abstract: Using synthetic oligodeoxyribonucleotides to prime the transcription of interferon mRNA and cDNA, we recently determined the mRNA sequence coding for the 47 amino-terminal amino acids of mature human fibroblast interferon (1).From this sequence, we have now synthesised an oligodeoxyribonucleotide that is homologous with the mRNA sequence coding for amino acids 42-45 and used it as a primer to selectively transcribe an interferon cDNA template. The sequence of the newly synthesised DNA predicted the sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…A cDNA clone corresponding to the mRNA encoding the major human fibroblast interferon (hIFN-,81) has been obtained and characterized (6)(7)(8). Recently, a genomic DNA segment specifying hIFN-,3l has been cloned and its sequence has been determined (9)(10)(11)(12)(13)(14) …”
mentioning
confidence: 99%
“…A cDNA clone corresponding to the mRNA encoding the major human fibroblast interferon (hIFN-,81) has been obtained and characterized (6)(7)(8). Recently, a genomic DNA segment specifying hIFN-,3l has been cloned and its sequence has been determined (9)(10)(11)(12)(13)(14) …”
mentioning
confidence: 99%
“…Briefly we consider that the observations reported by previous investigators (25)(26)(27)(28)(29)(30) were essentially correct but that the earlier interpretations of the then available data did not fully recognize the complexities involved in the structure and expression of human IFN-/~ genes. The IFN-/~ gene family, of which only IFN-/~I has been cloned and characterized convincingly (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), is dispersed in the human genome. We have shown earlier (12) that an IFN-/~I cDNA probe does not cross-hybridize IFN-B2 mRNA, even under rather relaxed hybridization conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide sequence analysis of about 100 bases, corresponding to the N-ternlinal region of the gene, confirmed that it coded for HuIFN-~1 of which the first 13 amino acids had been sequenced (Knight et af.~1980). The full sequence of the gene and hence of the derived protein was established independently by t\\lO other groups (Derynck et at.~1980a; Houghton et at., 1980) and published separately by the Japanese workers (Taniguchi et at., 1980a).…”
Section: Sources Of Dna For Cloning Of Ifn Genesmentioning
confidence: 99%